In Vivo Multimodal Magnetic Resonance Imaging Changes After N-Methyl-d-Aspartate-Triggered Spasms in Infant Rats - Minyoung Lee; Minyoung Lee; Mi-Sun Yum; Mi-Sun Yum; Dong-Cheol Woo; Woo-Hyun Shim; Woo-Hyun Shim; Tae-Sung Ko; Libor Velíšek; Libor Velíšek; Libor Velíšek (Frontiers in Neurology, 2018)
ObjectiveDespite the serious neurodevelopmental sequelae of epileptic encephalopathy during infancy, the pathomechanisms involved remain unclear. To find potential biomarkers that can reflect the pathogenesis of epileptic encephalopathy, we explored the neurometabolic and microstructural sequelae after infantile spasms using a rat model of infantile spasms and in vivo magnetic resonance imaging techniques.MethodsRats prenatally exposed to betamethasone were subjected to three rounds of intraperitoneal N-methyl-d-aspartate (NMDA) triggering of spasms or received saline injections (controls) on postnatal days (P) 12, 13, and 15. Chemical exchange saturation transfer imaging of glutamate (GluCEST) were performed at P15 and 22 and diffusion tensor imaging and additional spectroscopy (1H-MRI/MRS) of the cingulate cortex were serially done at P16, 23, and 30 and analyzed. Pathological analysis and western blotting were performed with rats sacrificed on P35.ResultsWithin 24 h of the three rounds of NMDA-induced spasms, there was an acute increase in the GluCEST (%) in the cortex, hippocampus, and striatum. When focused on the cingulate cortex, mean diffusivity (MD) was significantly decreased during the acute period after multiple spasms with an increase in γ-aminobutyric acid (GABA), glutamate, and glutamine N-acetylaspartate-plus-N-acetylaspartylglutamate (tNAA), total choline, and total creatine. The juvenile rats also showed decreased MD on diffusion tensor imaging and significant decreases in taurine, tNAA, and macromolecules-plus-lipids in the cingulate cortex. Pathologically, there was a significant reduction in glial fibrillary acidic protein, myelin basic protein, and neuronal nuclei expression in the cingulate cortex of rats with NMDA-induced spasms.SignificanceThese neurometabolic and microstructural alterations after NMDA-triggered spasms might be potential imaging biomarkers of epileptic encephalopathy.